Salinity stress on morphological and nutritional quality of Napier cultivars under hydroponic condition - Alam, MK; Sarker, NR; Nasiruddin, KM; Shohael, AM (Bangladesh Journal of Animal Science, 2017)
The study was conducted to determine the effect of salinity stress on morphological and nutritional quality of Napier cultivars in terms of biomass yield, tiller numbers, leaf number, tiller height, shoot presence or absence per cutting, leaf condition, dry matter (DM) and crud protein (CP) content under hydroponic condition. four Napier cultivars such as BLRI Napier-1, BLRI Napier-2, BLRI Napier-3 and BLRI Napier-4 were cultivated under hydroponic system developed by Bangladesh Agricultural Research Institute (BARI) with some modifications. All the selected cultivars were grown by using BARI standard hydroponic solution. Five salinity levels were considered as treatments such as 3, 4, 5, 6 and 7 dS m-1 using different NaCl concentrations corresponding to the nutrient solution which were noted as T1 to T5 and T0 was used as control where salinity level was 2.3 dSm-1. Four Napier cultivars were grown with 4 replications under each salinity condition and all the treatments were arranged in a Randomized Complete Block (RCB) design. Shoot presence or absence per cutting and leaf condition were determined weekly. The results revealed that the biomass yield, number of tillers, leaf numbers, tiller height, shoot presence or absence per cutting, leaf condition, and DM and CP content among all the cultivars were decreased linearly with the increased of salinity levels. On the basis of different morphological and nutritional parameters, tolerance level of different cultivars of Napier grass to salinity stress can be rated as: BLRI Napier-4>BLRI Napier-3 > BLRI Napier-2 >BLRI Napier-1. Further study need to determine the suitability for large scale adaptation under on-farm conditions. Bang. J. Anim. Sci. 2017. 46 (2): 102-108